Evaluation of Locoregional Recurrence Patterns Following Adjuvant (Chemo)Radiotherapy for Oral Cavity Carcinoma. Issue 4 (April 2020) - Waldram, R.; Taylor, A.E.; Whittam, S.; Iyizoba-Ebozue, Z.; Murray, L.; Frood, R.; Cardale, K.; Dyker, K.E.; Murray, P.; Ramasamy, S.; Sen, M.; Al-Qaisieh, B.; et al.
Abstract: Aims: To evaluate patterns of locoregional recurrence following adjuvant (chemo)radiotherapy for oral cavity squamous cell carcinomas. Materials and methods: One hundred and one patients who received adjuvant radiotherapy ± chemotherapy for oral cavity squamous cell carcinoma between 2013 and 2016 were analysed. For documented locoregional recurrence, recurrence imaging was deformably co-registered to the planning computed tomography scan. The volume of recurrence was delineated (Vrec). Vrec coverage by 95% of the corresponding planning target volume prescription dose was determined and the location compared with planning target volumes. Sites of recurrence were classified using a combined volume and centroid-based method: (A) central high dose, (B) peripheral high dose, (C) central low dose, (D) central peripheral dose, (E) extraneous. Results: The median follow-up was 36 months. Forty-three per cent and 53% of patients received radiotherapy to the ipsilateral neck only and bilateral neck, respectively. Three-year overall survival, disease-free survival, local control, regional control and distant metastases-free survival were 63.0, 65.6, 88.0, 85.1 and 85.3%, respectively. Of 10 episodes of primary site recurrences, five were type A, four type B and one was type E. Of 14 episodes of regional recurrence, five were type A, two type C, two type D and five type E. Five of 21 (24%) patients with oral tongue carcinoma with an undissected/unirradiated contralateral neck had a type E contralateral neck recurrence, including 2/11 with pN0, 1/4 with pN1 and 2/6 with pN2 disease. Conclusions: Marginal and out-of-field recurrences remain a significant pattern of failure. We advocate generous target delineation postoperatively and, for oral tongue carcinomas, a comprehensive approach with bilateral neck irradiation. Highlights: Locoregional recurrences are common for oral cavity carcinomas. Target selection/delineation is challenging for adjuvant radiotherapy. Analysis shows the occurrence of marginal and out-of-field recurrences. For oral tongue carcinomas the undissected/unirradiated contralateral neck is at risk. A generous approach to radiotherapy target selection/delineation is required.